A New Approach to Enhance E-mail Performance through POP3 Protocol - Al Bazar, Hussein; R., Sureswaran; O., Abouabdalla (2008)
E-mail system has become the most popular computer based method used to send and receive E-mail messages between the network clients inside or outside the local network.